2007
DOI: 10.1093/ejo/cjl069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nasal volume changes during rapid maxillary expansion using acoustic rhinometry and computed tomography

Abstract: The purpose of this study was to compare nasal volume changes using acoustic rhinometry (AR) and computed tomography (CT). The subjects were 10 children (6 girls and 4 boys, with an age range of 12-14 years) who required rapid maxillary expansion (RME) on the basis of their individual malocclusion. All patients were found to have normal nasal cavities following anterior rhinoscopic examination. AR and CT were undertaken at the start of treatment (t(1)) and 6 months after expansion (t(2)). Volume changes due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
25

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 20 publications
4
56
0
25
Order By: Relevance
“…16 Cephalograms, tomography, and rhinomanometry methods are used to examine the nasal airway and related dentofacial structures. 8 AR is a method that allows quick, painless, and noninvasive application and requires minimal patient cooperation. AR showed a reasonable correlation with CT in a cadaver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Cephalograms, tomography, and rhinomanometry methods are used to examine the nasal airway and related dentofacial structures. 8 AR is a method that allows quick, painless, and noninvasive application and requires minimal patient cooperation. AR showed a reasonable correlation with CT in a cadaver.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, computerized tomography (CT) has become very popular in the diagnosis of deformities and structures of the body, but the disadvantages of CT include exposure to radiation and high costs. 8 Acoustic rhinometry (AR) was introduced by Hilberg et al 9 in 1989 as a simple, noninvasive, and objective method for measuring the dimensions of the nasal cavity and nasal airway resistance. The principle of AR is based on the reflection of sound waves within the nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Using 3D simulation and modeling programs, Gö rgü lü et al 11 found a significant nasal volume increase of 12.14%. A significant increase in nasal volume was shown also using acoustic rhinometry; 9 Babacan et al 8 estimated this increase to be 13.80% without decongestant and 15.16% with decongestant, while others 12 found a significant increase of nasal cavity volume by 15.20% and nasopharynx volume by 10 concluded that RME is usually accompanied by increases in area and volume of the nasal cavity, and these changes remained stable 3 months after treatment. The nasal volume increase of 17% reported in this study was quite close to values published in previous studies.…”
Section: 7-121921mentioning
confidence: 95%
“…The nasal volume increase of 17% reported in this study was quite close to values published in previous studies. [8][9][10][11][12] Several articles focused on evaluating RME effects on MSV; Pangrazio-Kulbersh et al 4 noticed a significant increase of between 6% and 11%, while others 12 didn't find any significant difference in MSV. Maxillary volume modifications following RME have not been evaluated.…”
Section: 7-121921mentioning
confidence: 99%
See 1 more Smart Citation